Afatinib-refractory brain metastases from EGFR-mutant non-small-cell lung cancer successfully controlled with erlotinib: a case report. Issue 3 (March 2016) - Nonagase, Yoshikane; Okamoto, Kunio; Iwasa, Tsutomu; Yoshida, Takeshi; Tanaka, Kaoru; Takeda, Masayuki; Kaneda, Hiroyasu; Shimizu, Toshio; Tsurutani, Junji; Nakagawa, Kazuhiko
Abstract : Both afatinib and erlotinib are tyrosine kinase inhibitors that inhibit aberrant epidermal growth factor receptor (EGFR) signals in non-small-cell lung cancer (NSCLC). Afatinib is an irreversible inhibitor directed against EGFR, ErbB-2, and ErbB-4, whereas erlotinib is a reversible inhibitor directed against EGFR only. Although afatinib has been shown to be effective in the treatment for erlotinib-refractory and/or gefitinib-refractory central nervous system metastases from NSCLC, little is known about the efficacy of erlotinib for afatinib-refractory central nervous system metastases. In the present report we describe a case of EGFR mutation-positive NSCLC in which brain metastases developed during first-line afatinib treatment. Whole-brain radiation therapy and substitution of erlotinib for afatinib led to successful shrinkage of the brain metastases. Our report highlights the potential benefit of erlotinib for the management of brain metastases refractory over afatinib in patients with NSCLC.